2021
DOI: 10.5194/npg-28-93-2021
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of the iterative ensemble-based variational method in nonlinear problems

Abstract: Abstract. The behavior of the iterative ensemble-based data assimilation algorithm is discussed. The ensemble-based method for variational data assimilation problems, referred to as the 4D ensemble variational method (4DEnVar), is a useful tool for data assimilation problems. Although the 4DEnVar is derived based on a linear approximation, highly uncertain problems, in which system nonlinearity is significant, are solved by applying this method iteratively. However, the ensemble-based methods basically seek th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…One plausible explanation is the effect of the solar-wind dynamic pressure, which is pro-portional to N sw V 2 sw . As some studies have suggested that field-aligned currents around the auroral latitudes are influenced by the solar-wind dynamic pressure (Iijima and Potemra, 1982;Wang et al, 2006;Nakano et al, 2009;Korth et al, 2010), it is possible that the enhancement of the field-aligned currents increases the auroral electrojets. Some studies suggested that the solar-wind dynamic pressure induces temporal effects on the ionospheric convection (Ober et al, 2007;Boudouridis et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One plausible explanation is the effect of the solar-wind dynamic pressure, which is pro-portional to N sw V 2 sw . As some studies have suggested that field-aligned currents around the auroral latitudes are influenced by the solar-wind dynamic pressure (Iijima and Potemra, 1982;Wang et al, 2006;Nakano et al, 2009;Korth et al, 2010), it is possible that the enhancement of the field-aligned currents increases the auroral electrojets. Some studies suggested that the solar-wind dynamic pressure induces temporal effects on the ionospheric convection (Ober et al, 2007;Boudouridis et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, since the feedback of y AU,k−1 and y AL,k−1 are contained, the optimal β cannot be obtained by linear regression. We thus obtained β using the ensemblebased optimization method (Nakano, 2021).…”
Section: Echo State Networkmentioning
confidence: 99%
“…These two issues might be partially addressed by using larger ensemble member and adding additional iteration loops, e.g. iteratively resampling ensemble of emission inventory and forming new linear approximations at the outer-loops as suggested by Nakano (2021). These however will severely increase the computational cost and thus challenge the inversion of long-term ammonia emission estimates over China.…”
Section: Nh 3 Total Column Concentrationmentioning
confidence: 99%
“…However, since the feedback of y AU,k−1 and y AL,k−1 are contained, the optimal β cannot be obtained by linear regression. We thus obtained β using the ensemble-based optimization method (Nakano, 2021).…”
Section: Echo State Networkmentioning
confidence: 99%